A influência da dimensão da abertura de saída da cozinha/serviço no potencial de ventilação dos ambientes de edificações multifamiliares em Maceió-AL - Sacramento, Alexandre da Silva (2012)
The design of residential buildings should have as an important criteria, the adoption of bioclimatic principles, taking into consideration the local climate in order to potentize the desirable characteristics of this climate as a means to meet the requirements for human comfort. In hot and humid climate, such Maceió-AL climate, natural ventilation as design strategy, it is important to the renewal of the air environment, for cooling the building envelop, to minimize energy costs, and to provide satisfactory levels of human thermal comfort. The performance of natural ventilation is strongly linked to the characteristics of the opening in buildings, which influence the potential of ventilation indoors. To make the air movement inside the building happen, it is necessary inlet and outlet openings. Few studies have addressed the potential provided by the ventilation outlet openings. This study sought to estimate the natural ventilation potential of multifamily residential building in Maceió-AL, varying the size of outlet openings of the kitchen/service for two types of urban roughness. To that end, was defined a Maceió - AL typical multifamily building, form which were varied the outlet openings size in the percentage of 10%, 15% and 25% based on the floor area and the middle section area of the environment. The results show that the natural ventilation potential for air quality was satisfactory in all cases. In relation to the recovery of comfort by natural ventilation, the results based on the floor area were close to those based on the middle section of the environment. Despite of the proximity of results, the outlet openings based on the middle section of the environment had a better performance